دور النشاط البدني المكيف في التخفيف من فرط النشاط عند الطفل المصاب بطيف التوحد درجة متوسطة دراسة ميدانية من المركز النفسي البيداغوجي 2 بالاغواط - جلال حطاب; عماد الدين روتال; باهي سلامي (My University, 2023)
The idea of the research revolves around the application of adapted physical activities for a sample of moderately autistic children who suffer from hyperactivity in order to discourage, direct or reduce it. Finally, and to consider whether physical activity has a role in mitigating hyperactivity in the autistic child of average degree, an attempt by us to reduce the problems arising from the problem of hyperactivity in the autistic child and the possibility of reducing distraction and reducing impulsivity, which leads the child to harm himself and others, Therefore, we tried to reach our goals by applying two adapted activities:  Jumping inside the rings.  Walking in the maze. We chose the Psychological Pedagogical Center for Mentally Handicapped Children -2- in Laghouat to apply this study, on a sample consisting of ten (10) children, whom we divided into two groups (experimental and control). following the experimental method, And measure the hyperactivity of children of the autism spectrum of the middle degree, and then we compared the results of the pre and post test of the scalek The results confirmed the significant role of adapted physical activity in reducing hyperactivity in a moderately autistic child The biggest goal of our research is to contribute to facilitating the sponsorship process by removing or mitigating the biggest obstacle to its success, which is hyperactivity, through adapted physical activities. Keywords: adapted physical activities/ hyperactivity/ autism spectrum/ children.